2016
DOI: 10.1002/jeab.222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the discriminative stimulus effects of lorcaserin in rats

Abstract: Lorcaserin is approved by the Food and Drug Administration for treating obesity and is under consideration for treating substance use disorders; it has agonist properties at serotonin (5-HT)2C receptors and might also have agonist properties at other 5-HT receptor subtypes. This study used drug discrimination to investigate the mechanism(s) of action of lorcaserin. Male Sprague-Dawley rats discriminated 0.56 mg/kg i.p. lorcaserin from saline while responding under a fixed-ratio 5 schedule for food. Lorcaserin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Although the capacity of a 5-HT 2C receptor antagonist (SB242084) to at least partially inhibit the effects of lorcaserin on drug self-administration ( Higgins et al, 2012 ; Harvey-Lewis et al, 2016 ; Neelakantan et al, 2017 ) suggests that these effects are mediated by the 5-HT 2C receptor, the single-dose design of these experiments did not allow for the nature of the antagonist effects to be characterized (e.g., competitive and surmountable, irreversible, etc.). It is also important to note that these studies reported decreases in drug self-administration at doses of lorcaserin (∼0.6–1 mg/kg) that are ∼20- to 30-fold larger than those required to induce yawning, a 5-HT 2C receptor-mediated effect, and comparable to those that have been shown to produce 5-HT 2A receptor-mediated effects in rats ( Serafine et al, 2015 , 2016 ). Moreover, because previous studies have examined only the interactions between lorcaserin and 5-HT 2C antagonists, it is currently unclear whether the actions of lorcaserin at other 5-HT receptors (e.g., 5-HT 2A and 5-HT 1A receptors) also contribute to the capacity of lorcaserin to decrease the reinforcing effects of stimulant drugs.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although the capacity of a 5-HT 2C receptor antagonist (SB242084) to at least partially inhibit the effects of lorcaserin on drug self-administration ( Higgins et al, 2012 ; Harvey-Lewis et al, 2016 ; Neelakantan et al, 2017 ) suggests that these effects are mediated by the 5-HT 2C receptor, the single-dose design of these experiments did not allow for the nature of the antagonist effects to be characterized (e.g., competitive and surmountable, irreversible, etc.). It is also important to note that these studies reported decreases in drug self-administration at doses of lorcaserin (∼0.6–1 mg/kg) that are ∼20- to 30-fold larger than those required to induce yawning, a 5-HT 2C receptor-mediated effect, and comparable to those that have been shown to produce 5-HT 2A receptor-mediated effects in rats ( Serafine et al, 2015 , 2016 ). Moreover, because previous studies have examined only the interactions between lorcaserin and 5-HT 2C antagonists, it is currently unclear whether the actions of lorcaserin at other 5-HT receptors (e.g., 5-HT 2A and 5-HT 1A receptors) also contribute to the capacity of lorcaserin to decrease the reinforcing effects of stimulant drugs.…”
Section: Introductionmentioning
confidence: 83%
“…Preclinical studies demonstrating that lorcaserin can decrease the ongoing self-administration of drugs with diverse mechanisms of action (e.g., nicotine, alcohol, cocaine, methamphetamine, and oxycodone) suggest that lorcaserin might also have utility as a pharmacotherapy for addiction. Although studies with 5-HT 2C receptor antagonists ( Higgins et al, 2012 ; Harvey-Lewis et al, 2016 ; Neelakantan et al, 2017 ) suggest that the capacity of lorcaserin to decrease drug self-administration is mediated by 5-HT 2C receptors, the doses of lorcaserin typically required to decrease drug self-administration are ∼20- to 30-fold larger than those required to induce 5-HT 2C receptor-mediated behavioral effects (e.g., yawning) and are comparable to those that produce 5-HT 2A receptor-mediated behavioral effects ( Serafine et al, 2015 , 2016 ) and to decrease responding for food ( Higgins et al, 2012 ; Briggs et al, 2016 ; Collins et al, 2016b ), raising the possibility that other 5-HT receptor subtypes are also contributing to the effectiveness of lorcaserin to decrease drug self-administration. Accordingly, the current study sought to characterize the relative contribution of actions at 5-HT 2C , 5-HT 2A , and 5-HT 1A receptors to the effectiveness of lorcaserin to decrease stimulant self-administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of note, however, that lorcaserin also has activity at other 5-HT receptors. In this regard, a recent drug discrimination study found that the 5-HT 1A agonist, 8-OH-DPAT, and the selective 5-HT 2A agonist, DOM, engendered lorcaserin-like responding in rats trained to discriminate lorcaserin suggesting a role of 5-HT 1A and 5-HT 2A receptors in the behavioral effects of lorcaserin (Serafine et al, 2016). These results suggest that the role of various 5-HT receptor subtypes in lorcaserin’s therapeutic effects require further examination and highlight the importance of receptor-subtype selective pharmacological manipulations that might lead to medications with better safety and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, its better pharmacological profile toward 5-HT 2C Rs, the differences between 0.3 and 3 mg/kg lorcaserin could also imply the recruitment of additional sites. Lorcaserin displays a higher affinity for 5-HT 2C Rs (Ki = 15 nM) compared to 5-HT 2A Rs (112 nM) and 5-HT 2B Rs (174 nM, acting as an antagonist) ( Thomsen et al, 2008 ), but previous data have reported that lorcaserin could recruit 5-HT 1A/2A Rs in behavioral responses such as forepaw treading and drug discrimination ( Serafine et al, 2015 ; Serafine et al, 2016 ). A brief behavioral evaluation of our rats receiving lorcaserin indicated that rats displayed purposeless oral movements at the low dose, as expected from the 5-HT 2C Rs agonist profile ( Gong et al, 1992 ; Lagiere et al, 2013 ; Navailles et al, 2013b ; Kreiss and De Deurwaerdere, 2017 ).…”
Section: Discussionmentioning
confidence: 99%